From Tagalog to English: Pupils’ Writing Proficiency Levels After Three Years in Mother Tongue-Based Multilingual Education - de Lemios, Ronald O. (Journal of Community Development Research (Humanities and Social Sciences); Vol 16 No 3 (2023): July - September 2023DO - 10.14456/jcdr-hs.2023.29, 2023)
The study aimed to investigate the impact of Mother Tongue-Based Multilingual Education (MTB-MLE) on students’ writing skills in their first language (L1), Tagalog, and explore whether their proficiency in L1 contributes to their second language (L2) writing. This study employed a conceptual framework based on language acquisition and bilingual education theories, implying that proficiency in the first language positively impacts second language writing abilities, while implementing MTB-MLE improves overall writing skills. A descriptive-correlational research design was employed, and data were gathered from 135 Filipino Grade 5 pupils who took Tagalog (L1) and English (L2) writing tests. The students came from nine small elementary schools in Paracale, Camarines Norte, Philippines and underwent the same MTB-MLE treatment from Grades 1 to 3. During the exams, they were given two writing tasks in Tagalog and English, with three question options to choose from. This allowed them to select a topic they were comfortable with, including personal experiences during the pandemic and questions from Grade 5 textbooks to ensure reliability. Participants expressed their opinions and discussed their responses within a 150-word limit. Their compositions were evaluated using modified Tagalog and English rubrics provided by DepEd, which employed a 4-point scale representing Beginning, Developing, Accomplished, and Exemplary proficiency levels. These rubrics assessed four key writing elements: content, organization, vocabulary, and conventions. The evaluators used these elements as criteria to evaluate the student’s work. The study’s findings showed that students performed better in their L1 than in their L2, indicating a significant discrepancy in writing proficiency levels between L1 and L2. The students’ L2 writing outputs were brief, disorganized, and filled with grammatical errors, while they also failed their Tagalog and English writing tests, implying that they could not apply the skills they acquired from MTB-MLE to improve their L1 and L2 writing outputs. The results of the study, however, have some limitations. The study cannot identify the factors that hinder students from improving their writing skills in both languages. Furthermore, given the prevalence of different regional languages, the study’s findings cannot be generalized to other parts of the country. Therefore, the researcher recommends further investigating the factors influencing pupils’ writing development in other regions with diverse L1 and L2 backgrounds. Keywords: Writing Proficiency, First Language, Second Language, MTB-MLE